World Economic Prospects. (29th November 2016) - Unknown
Abstract : Overview: Trump wins, but the world doesn't end Our world GDP growth forecast for 2016 is unchanged this month at 2.2%, which would be the lowest since 2009. For 2017, we have lowered our forecast to 2.5% from 2.6% previously. Yet short‐term global activity indicators point to a pickup in activity in Q4 this year. The global manufacturing PMI rose to its highest in two years, and the composite index – which includes services – also strengthened. And there are tentative signs of a modest recovery in world trade volumes. Donald Trump's victory in the US elections has, however, added to the uncertainty about the economic outlook. At this stage, it is unclear which of the policies he promised during the campaign will be enacted. Currently, the markets have focused on his promises for tax cuts and a big expansion in infrastructure investment, and bond yields have risen in anticipation of stronger growth and higher inflation. However, in addition to measures to increase deportation of illegal immigrants, Trump has also threatened to impose tariffs on Chinese and Mexican imports, which could trigger retaliatory action and undermine business confidence globally. Brexit has taught us not to overreact to such events and our baseline forecast is little changed from last month given the lack of clarity about the policy outlook. Our scenario analysis suggests that if Trump continues to dial back on his rhetoric on trade protection and focuses on tax cuts/infrastructure spending, then he could boost US growth to 3% by 2018, whereas full implementation of his tariff proposals could trigger a recession. We continue to think the Fed will raise rates in December; only if market reaction turns more adverse do we think the Fed will delay. Any Trump‐induced weakness in world growth may make it easier for China's policymakers to scale back their growth ambitions, although they would likely offset some of the impact via additional fiscal expansion. The most immediate impact on European policy‐making, in our view, is that the ECB is now less likely to announce a tapering of bond purchases from April at its December meeting.